Gerhana dan Keharusan Kosmologis Manusia: Tinjauan Filsafat Wujud (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2017)
AbstractEclipse is a natural event that could not be avoided, Indeed it has become a part of life that merged into one in the solar system. His existence adorns and completes the universe. Eclipse is a natural phenomenon that quickly change the atmosphere, the weather becomes dark. This simple phenomenon is a natural event that periodically often occurs in the world. In addition, the natural phenomenon of the eclipse is a part of authority of God Allah, The almighty. So, this article firstly describes about kind of eclipse; the solar eclipse and lunar eclipse. Then the article describes philoshopically the connection of this eclipse with human\s cosmology. There was closely related between human and eclipse. Everyone is the Wali of God Allah (Khalifah fi al-Ardhi) which had been sent to guard and manage the universe. Cosmologically, human was called as micro cosmos of the cosmos existing in the whole solar system. So the relationship between humans and other creatures was very close. And a person as a servant of God Allah whose reason (logics) and heart (qalb) is expected to do self- reinforcement (rationalization and also mukasyafah) toward creatures, including the phenomenon of eclipse. In short, we khnow then the position of human toward God Allah.AbstrakGerhana adalah peristiwa alam yang tidak bisa dihindari, memang sudah menjadi bagian kehidupan yang menyatu menjadi satu di tata surya. Keberadaannya menghiasi dan melengkapi alam semesta. Eclipse adalah fenomena alam yang dengan cepat mengubah atmosfer, cuaca menjadi gelap. Fenomena sederhana ini adalah peristiwa alam yang secara berkala sering terjadi di dunia. Selain itu, fenomena alam gerhana adalah bagian dari otoritas Allah Allah SWT. Jadi, artikel ini pertama kali menjelaskan tentang jenis gerhana; gerhana matahari dan gerhana bulan. Kemudian artikel tersebut menggambarkan secara filosofis hubungan gerhana ini dengan kosmologi manusia. Ada kaitan erat antara manusia dangerhana. Setiap orang adalah Wali Allah (Khalifah fi al-Ardhi) yang telah dikirim untuk menjaga dan mengelola alam semesta. Secara kosmologis, manusia disebut sebagai mikro kosmos dari kosmos yang ada di seluruh tata surya. Jadi hubungan antara manusia dan makhluk lain sangat dekat. Dan seseorang sebagai hamba Allah Allah yang alasannya (logika) dan hatinya (qalb) diharapkan untuk melakukan penguatan diri (rasionalisasi dan juga mukasyafah) terhadap makhluk, termasuk fenomena gerhana. Singkatnya, kita khnow maka posisi manusia terhadap Allah Allah. Kata kunci: Eclipse (Sun, Moon), Kosmologi dan Manusia.